Critical junctures and city development: a brief retrospect of Chongqing’s planning history, 1949-2010 - Jiang, Mian (International Planning History Society Proceedings, 2018)
Southwest China’s Chongqing is a city with unique development history which experienced critical junctures. This study collected and organized political, economic and cultural events in Chongqing from 1949 to 2010, and then analysed how its city planning responded to those critical junctures, and evaluate whether it was successful or not; furthermore, it traced the evolution of motive forces in Chongqing. The analysis has led us to the conclusion that critical junctures constituted pivotal motive forces in Chongqing’s urbanization; generally, each version of Master Plans responded them effectively and timely, especially by giving the priority to natural geography and continually developing the polycentric structure at different scale. The result of this study shows that Chongqing has built a comprehensive development framework for settlement hierarchy structure, transportation, economy and ecology. For the future, it should pay more attention to improve its infrastructure, conserve its historic heritage, strengthen its identity as a city of mountain and river, and achieve more sustainable development both ecologically and socially. Moreover, besides making sure that politic and economic forces fulfil their role, decision makers should also value social forces, make multiple objectives, exercise public participation and achieve social justice in the policy making and implementing process.